2013
DOI: 10.1155/2013/634207
|View full text |Cite
|
Sign up to set email alerts
|

Association ofCILP2andACEGene Polymorphisms with Cardiovascular Risk Factors in Slovak Midlife Women

Abstract: The aim of this study is to assess the association of two polymorphisms, the cartilage intermediate layer protein 2 (CILP2) G/T and angiotensin converting enzyme (ACE) I/D, with blood pressure and anthropometrical and biochemical parameters related to the development of cardiovascular disease. The entire study sample comprised 341 women ranging in age from 39 to 65 years. The CILP2 genotypes were determined by PCR-RFLP and the ACE genotypes by PCR. The Bonferroni pairwise comparisons showed the effect of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
13
1
Order By: Relevance
“…Rašlová K, et al's report on the association between CILP2 polymorphism and FER(HDL) supports its role in lipid metabolism [22] . While in other reports, the relationship between CILP2 polymorphism and lipid metabolism was not yet discovered [23] , nor in the Japanese population [24] or Slovak Midlife women [25] . However, Lenka et al indicated that the minor T allele in the CILP2 gene was associated with lower LDL-C, apoB, and atherogenic indices and higher HDL-C levels [25] .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Rašlová K, et al's report on the association between CILP2 polymorphism and FER(HDL) supports its role in lipid metabolism [22] . While in other reports, the relationship between CILP2 polymorphism and lipid metabolism was not yet discovered [23] , nor in the Japanese population [24] or Slovak Midlife women [25] . However, Lenka et al indicated that the minor T allele in the CILP2 gene was associated with lower LDL-C, apoB, and atherogenic indices and higher HDL-C levels [25] .…”
Section: Discussionmentioning
confidence: 85%
“…While in other reports, the relationship between CILP2 polymorphism and lipid metabolism was not yet discovered [23] , nor in the Japanese population [24] or Slovak Midlife women [25] . However, Lenka et al indicated that the minor T allele in the CILP2 gene was associated with lower LDL-C, apoB, and atherogenic indices and higher HDL-C levels [25] . This result was by the study in the Singaporean population ranging from 40 to 80 years of age [26] .…”
Section: Discussionmentioning
confidence: 85%
“…According to Kathiresan et al [8] , in Caucasian individuals analyzed, rs16996148 variant of CILP2 gene had a reducing role in triglyceride and LDL-C level. While in other reports, the relationship between CILP2 polymorphism and lipid metabolism was not yet discovered [18] , nor in Japanese population [19] or in Slovak Midlife women [20] . However, Lenka et al indicated that the minor T allele in CILP2 gene was associated with lower LDL-C, apoB, and atherogenic indices and higher HDL-C levels [20] .…”
Section: Discussionmentioning
confidence: 85%
“…While in other reports, the relationship between CILP2 polymorphism and lipid metabolism was not yet discovered [18] , nor in Japanese population [19] or in Slovak Midlife women [20] . However, Lenka et al indicated that the minor T allele in CILP2 gene was associated with lower LDL-C, apoB, and atherogenic indices and higher HDL-C levels [20] . This result was in accordance with the study in Singaporean population ranging from 40 to 80 years of age [21] .…”
Section: Discussionmentioning
confidence: 85%
“…According to Kathiresan et al [8] , in Caucasian individuals analyzed, rs16996148 variant of CILP2 gene had a reducing role in triglyceride and LDL-C level. While in other reports, the relationship between CILP2 polymorphism and lipid metabolism was not yet discovered [20] , nor in Japanese population [21] or in Slovak Midlife women [22] . However, Lenka et al indicated that the minor T allele in CILP2 gene was associated with lower LDL-C, apoB, and atherogenic indices and higher HDL-C levels [22] .…”
Section: Discussionmentioning
confidence: 85%